2002
DOI: 10.1002/poc.574
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative approach to the Menschutkin reaction of benzylic systems

Abstract: The quaternization reactions of substituted (Z)-benzyl (X)-benzenesulfonates with substituted (Y)pyridines were investigated in acetonitrile at 35°C. The magnitudes of the Hammett reaction constants r X , r Y and r Z indicate that a stronger nucleophile leads to a lesser degree of bond breaking. In addition, a better leaving group is accompanied by a lesser degree of bond formation. Application of multi-Hammett interactions, j YZ j >j XY j >j XZ j, predicts that these Menschutkin-type reactions are dissociativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…There have been several examples in the literature of Menschuktin reactions with very deactivated nucleophiles, and/or highly activated electrophiles, that exhibit both S N 1 and S N 2 character. [22][23][24][25][26][27][28] After testing several Menschutkin reactions of benzyl halides with pyridines, the reaction between the bromide 1b and the deactivated pyridine 2b was found to show a detectable first order contribution to the substitution process. Hence, the reaction was carried out over a range of nucleophile 2b concentrations for each of a series of different mole fractions of [Bmim][N(CF 3 SO 2 ) 2 ] in acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several examples in the literature of Menschuktin reactions with very deactivated nucleophiles, and/or highly activated electrophiles, that exhibit both S N 1 and S N 2 character. [22][23][24][25][26][27][28] After testing several Menschutkin reactions of benzyl halides with pyridines, the reaction between the bromide 1b and the deactivated pyridine 2b was found to show a detectable first order contribution to the substitution process. Hence, the reaction was carried out over a range of nucleophile 2b concentrations for each of a series of different mole fractions of [Bmim][N(CF 3 SO 2 ) 2 ] in acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous kinetic studies on the formation of N ‐alkyl‐X‐pyridinium ions from substituted pyridines (X‐pyridines) and neutral substrates have been published [2a–e] . Mayr and coworkers investigated nucleophilicities and basicities of some X‐pyridines in the reactions with different benzhydryl cation in dichloromethane and water [3] .…”
Section: Introductionmentioning
confidence: 99%
“…As part of our interest in modeling routes for metal-mediated C–X bond formation (where X is a halide or heterofunctional group), we seek to compare and contrast metal-mediated variants of classic organic routes . In one especially comprehensive study that incorporated theory and experiment, Yoh and co-workers investigated the nucleophilic attack of substituted (Q)-benzyl-(X)-benzenesulfonates with (Y)-pyridines to determine the relative effects of changing the electronic properties of the leaving group (benzenesulfonate), electrophile (benzyl group), and nucleophile (pyridine) on the rate (Scheme ) . They found that changing the electronic properties of the pyridine nucleophile (Y) had the largest effect on the rate of reaction, while modifying the electronic properties of the benzenesulfonate leaving group (X) had a similar but slightly diminished effect on the rate of S N 2 substitution.…”
Section: Introductionmentioning
confidence: 99%
“…To wit, even the largest Hammett ρ value determined for changing the benzyl group was smaller than the smallest ρ calculated for either the benzenesulfonate leaving group or the pyridine nucleophile. The study by Yoh et al thus suggests an order of importance for what parameters most affect this organic S N 2 reaction in polar, aprotic media: viz., nucleophile > leaving group ≫ electrophile …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation